Performance characteristics of DOAC dipstick in determining direct oral anticoagulants in urine - Harenberg, Job; Martini, Andrea; Du, Shanshan; Krämer, Sandra; Weiß, Christel; Hetjens, Svetlana (Clinical and applied thrombosis, hemostasis, 2021)
Testing for direct oral anticoagulants (DOACs) in patient urine may facilitate medical treatment decisions. The aim of this study was to investigate interobserver variability by 2 independent observers compared to laboratory staff in the visual interpretation of factor Xa (DXI) and thrombin inhibitors (DTI) using the DOAC Dipstick test. We also examined whether test pads reacted to other anticoagulants and abnormal urine colors. The colors of the DOAC Dipstick direct factor Xa inhibitor and thrombin inhibitor pads were interpreted with 100% accuracy (95% confidence interval 0.862 to 1.000) for urine samples from persons treated with apixaban (n = 26), rivaroxaban (n = 24), and dabigatran (n = 29) and without anticoagulant therapy (n = 29). The factor Xa and thrombin inhibitor pads did not interact with heparin, nadroparin, fondaparinux, or coumadin. One µg/mL r-Hirudin and 6 µg/mL argatroban interacted with the DTI pad; however, this is unlikely to cause clinical problems because dabigatran is unlikely to be administered together with r-Hirudin and argatroban in clinical circumstances. Abnormal urine color was reliably detected by the urine color pad, so can prevent false interpretation of the DOAC Dipstick pad colors. In conclusion, we have demonstrated that interobserver variability when interpreting the DOAC Dipstick test strip is low and that factor Xa and thrombin inhibitor pads do not react to other anticoagulants such as heparins and coumadin. R-Hirudin and argatroban can be detected by the thrombin inhibitor pad and abnormal urine colors can be detected by the urine color pad to prevent false interpretation of the results in patient urine samples.
Gesehen am 22.07.2021